Case-Based Textbook of Echocardiography (Springer International Publishing, 2018)
This volume is a step-by-step educational textbook covering basic to advanced echocardiography that is helpful to all residents, fellows and clinicians in cardiology, internal medicine, cardiac surgery, interventional cardiology and pediatric cardiology. It is designed to rationalise and instruct readers on the rapid development in echocardiographic techniques, including real-time three-dimensional echocardiography, strain/strain rate imaging, and speckle tracking, which have greatly expanded the capabilities of cardiac imaging while overshadowing the importance of the basics of echocardiography. Case-Based Textbook of Echocardiography offers a comprehensive review of echocardiography from basic to advanced, including practical points from recently published ASE/EACVI guidelines and explanatory movies and figures. It will be of great interest for all trainee cardiologists and provide experienced echocardiographers with a thorough reference on the topic.